COMPARATIVE STUDY: HEALTH RISK BEHAVIOUR IN URBAN AND RURAL INDONESIAN ADOLESCENTS - Vionalita, Gisely; Ismail, Zalina (Universitas Airlangga, 2025)
Introduction: In 2019, the prevalence of cigarette smoking among adolescents in Indonesia increased to 18.8%. Aim: To assess health risk behaviours among Indonesian students in both urban and rural areas. Methods: This study's survey items, were developed using items questionnaire that focuses on smoking, eating, socioeconomic status (SES), and social relationships among teenagers aged 14 to 18. The study used two separate, demographically and culturally varied school-based populations. Results: The study found that teenagers in urban areas were more likely to smoke cigarettes, whilst adolescents in rural areas were more likely to practice healthy eating habits. Significant disparities in socioeconomic level (P 0.05) and social interactions (P 0.05) were also discovered, which may have an impact on the health risk behaviours seen in teenagers. The development of focused therapies and public health initiatives to address teenage health risk behaviours will benefit from these findings. Conclusion: More study is necessary to further understand the relationship between risk factors and health behaviours in both urban and rural teenagers in Indonesia. This will make it possible to find efficient preventive techniques and plans adapted to pupils' particular environments and cultural backgrounds.